2016
DOI: 10.1093/pcp/pcv209
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis FH1 Formin Affects Cotyledon Pavement Cell Shape by Modulating Cytoskeleton Dynamics

Abstract: Plant cell morphogenesis involves concerted rearrangements of microtubules and actin microfilaments. We previously reported that FH1, the main Arabidopsis thaliana housekeeping Class I membrane-anchored formin, contributes to actin dynamics and microtubule stability in rhizodermis cells. Here we examine the effects of mutations affecting FH1 (At3g25500) on cell morphogenesis and above-ground organ development in seedlings, as well as on cytoskeletal organization and dynamics, using a combination of confocal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
76
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(88 citation statements)
references
References 77 publications
10
76
2
Order By: Relevance
“…Kymograms are sometimes used to qualitatively demonstrate plant cytoskeletal dynamics (e.g. [2226]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kymograms are sometimes used to qualitatively demonstrate plant cytoskeletal dynamics (e.g. [2226]).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, quantitative analysis of cytoskeletal dynamics remains challenging, especially in the case of rapidly changing and often weakly labeled actin structures, and techniques involving manual tracking or counting of individual filaments or filament bundles thus remain the method of choice (e.g. [23, 25, 26, 33, 34]). Such a manual approach is usually very laborious and may be prone to observer bias (which can be eliminated by a blinded study design involving an evaluator who does not know which sample is which).…”
Section: Introductionmentioning
confidence: 99%
“…24 We recently reported that impairment of formin function in Arabidopsis (either by mutations in the FH1 locus or by pharmacological intervention) leads to increased complexity of cotyledon pavement cell shape, associated with stabilization and bundling of microfilaments, reduced density of fine cortical actin meshwork, and increased dynamics of cortical microtubules. 25 Thus, formins, members of an evolutionarily ancient family of eukaryotic proteins possessing the FH2 domain whose dimer can nucleate actin, may play a key part in such actin-microtubule co-ordination. Indeed, formins often participate in microtubule organization in both metazoans and plants (reviewed in refs.…”
mentioning
confidence: 99%
“…In Arabidopsis, FH1 is the most ubiquitously expressed Class I formin during vegetative development (see refs. 25,27). This may explain the similarity of pavement cell shape changes caused by fh1 loss-of-function mutation and by general inhibition of formin-dependent actin polymerization by treatment with the SMIFH2 compound.…”
mentioning
confidence: 99%
See 1 more Smart Citation